Digital Diplomacy: Hololive Indonesia and Virtual Youtuber (Vtuber) as Indonesia's New Public Diplomacy - Gustav Gallennius; Akil, Salsabila Andi (Yayasan Ilomata, 2024)
Globalization has influenced the international political system, including the diplomacy scene. The advent of the internet has resulted in new public diplomacy that emphasizes network and soft power. Virtual YouTubers have emerged as a global phenomenon, becoming new Japanese soft power. This research aim to explain the Virtual Youtuber’s potential as new power in the realm of new public diplomacy, emphasizes on the development of long-term relationship and two-way communication differs from traditional public diplomacy, focused on propaganda and one-way communication. Through qualitative descriptive analysis method and content analysis technique, this research focus on the role of VTubers, specifically Hololive Indonesia, as a new power in Indonesian new public diplomacy characterized by three key features: (1) a branding-oriented approach; (2) the utilization of new media and the establishment of long-term relationships; and (3) the involvement of foreign viewers as actors, fostering non-hierarchical relationships among these actors. The study's findings show that Virtual Youtuber could be the actor in the realm of new public diplomacy. As in the case of Hololive Indonesia through the promtoion of Indonesia branding as a multicultural and diverse nation. The utilization of YouTube as a new media platform, combined with features like live chat, super chat, and subscription, allows VTubers to establish long-term relationships with their viewers. Furthermore, these features allow Hololive Indonesia's viewers act as actor to actively contribute in the content produced by VTubers, establishing non-hierarchical relationships between them.